Uniform system of accounts and expense dictionary for small hotels, motels, and motor hotels / Smaller properties advisory council of the american hotel & motel association - Smaller properties advisory council of the american hotel & motel association
Uniform system of accounts and expense dictionary for small hotels, motels, and motor hotels